(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The invention of the article uzbeklarning the marriage of Bulgan sovhilik Bilan berklik urf-the custom of Andijan region wintkazilgan ethnographic researcher based on yeritib berilgan.